Predictability Stock Return with Debt to Equity Ratio, Return on Assets and Returns on Equity: An Empirical Study of listed Consumer Goods Sector in IDX - Widyaningsih, Ika Utami; Fitriyani, Fara (PT Larva Wijaya Penerbit, 2023)
The purpose of this research is to analyze the factors that influence to the stock returns on Indonesian Stock Exchange in consumer goods sector for the 2018-2022 period, such as capital structure and profitability. Capital structure proxied by debt to equity ratio (DER) and profitability proxied by return on assets (ROA) and return on equity (ROE). The population of this study were 49 companies that listed on consumer goods sector. The data analyze using regression analysis. Hypothesis testing is done by t test and F test with a significant level < 0.05. The results showed that the debt to equity ratio (DER) had a negative and significant effect on stock returns,Return on Assets (ROA) had a positive effect on stock returns, and Return on Equity (ROE) had a positive effect on stock returns.Simultaneously, Debt to Equity Ratio (DER), Return on Assets (ROA), and Return on Equity (ROE) have an effect on stock returns.